The drama of the lost disciples - Jowett, George Fiusdale (Covenant Pub. Co, 1961)
Familiarity with the Gospel record often blinds people's minds to the terrific events surrounding the life, death and resurrection of our Lord. No less impressive are the events following soon after His resurrection when Joseph of Arimathea and his fellow-Christians made their journey westward to plant the faith among the people of dispersed Israel. The wealth of evidence collected by the author throws into high relief the dramatic struggle between the forces of good and evil during that crucial first century of the Christian era.